Development and Integration a Smart Trolley with Automatic Billing and Inventory Control System - CH. , Brahmaiah; S. , Shanthi (International Journal of Psychosocial Rehabilitation, 2020)
In metro cities on public holidays, we will see a huge rush at shopping malls. When there are big sales and discounts, that becomes even more. People buy a variety of items in just a few days and place them in the trolley. After one will approach the counter for billing purposes during the total purchase. The cashier prepares the bill by using the barcode reader, which is a time-consuming operation. This results in long queues on the billing counters. This project introduces an idea to develop a system for solving the above problem in shopping malls. Both items in the mall should be labeled with RFID tags to achieve this, and all trolleys should be equipped with an RFID reader and an LCD screen. When any product is put in the trolley, the tag will automatically be identified, and the item name and cost will be shown on the LCD, adding the cost to the total bill. When we wish to remove the product from the trolley, you may take the product away, and the quantity of that particular product is deducted from the total quantity, and the same information is transferred to the central billing unit through the Zigbee module. Therefore, the payment can be handled in the trolley itself, saving the customers a lot of time.